2009
DOI: 10.1259/dmfr/30077669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic resonance imaging on microleakage of amalgam restorations: anin vitrostudy

Abstract: The results of this study suggest that MRI is not a completely safe technique in patients with amalgam restorations. It was shown that the main effect of fields led to the appearance of thermoelectromagnetic convection, which is responsible for the enhancement of the diffusion process, grain boundary migration and vacancy formation resulting in microleakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
6
39
4
1
Order By: Relevance
“…Therefore, similar to the previous studies, we have used common visual microleakage scale for evaluation of microleakage. It is worth mentioning that a blot-like dye penetration along dentinal tubules was observed in this study which was similar to the pattern observed by Shahidi et al in our previous study (12) . However, Yilmaz and Misirlioglu have observed a linear dye penetration pattern (14) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, similar to the previous studies, we have used common visual microleakage scale for evaluation of microleakage. It is worth mentioning that a blot-like dye penetration along dentinal tubules was observed in this study which was similar to the pattern observed by Shahidi et al in our previous study (12) . However, Yilmaz and Misirlioglu have observed a linear dye penetration pattern (14) .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, there are only a few studies which examined the effect of MRI on the microleakage of amalgam restorations (12)(13)(14) . While the results of two out of three of these studies suggest that MRI is not a completely safe technique in patients with amalgam restorations, Okgun et al concluded that MRI does not increase microleakage of amalgam restorations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other research finding, the mercury released from dental amalgams was significant in patients' saliva and urine samples after being exposed to magnetic MRI fields (0.23T), and mobile devices [22]. The effect of magnetic fields emitted from MRI with identical conditions on teeth restored with different commercial amalgams showed different microleakages of mercury in vitro conditions (where human teeth were studied in artificial saliva) [23]. Briefly after, the role of MRI irradiation (1.5T) in the release of mercury in the urine of students with restored teeth was reported [24].…”
Section: Introductionmentioning
confidence: 82%